Illuminating the dark metabolome of Pseudo‐nitzschia –microbiome associations - Irina Koester; Zachary A. Quinlan; Louis‐Félix Nothias; Margot E. White; Ariel Rabines; Daniel Petras; John K. Brunson; Kai Dührkop; Marcus Ludwig; Sebastian Böcker; Farooq Azam; Andrew E. Allen; et al. (Environmental Microbiology, 2022)
The exchange of metabolites mediates algal and bacterial interactions that maintain ecosystem function. Yet, while thousands of metabolites are produced, only a few molecules have been identified in these associations. Using the ubiquitous microalgae Pseudo‐nitzschia sp., as a model, we employed an untargeted metabolomics strategy to assign structural characteristics to the metabolites that distinguished specific diatom‐microbiome associations. We cultured five species of Pseudo‐nitzschia , including two species that produced the toxin domoic acid, and examined their microbiomes and metabolomes. A total of 4826 molecular features were detected by tandem mass spectrometry. Only 229 of these could be annotated using available mass spectral libraries, but by applying new in silico annotation tools, characterization was expanded to 2710 features. The metabolomes of the Pseudo‐nitzschia ‐microbiome associations were distinct and distinguished by structurally diverse nitrogen compounds, ranging from simple amines and amides to cyclic compounds such as imidazoles, pyrrolidines and lactams. By illuminating the dark metabolomes, this study expands our capacity to discover new chemical targets that facilitate microbial partnerships and uncovers the chemical diversity that underpins algae‐bacteria interactions.

Synthetic algal-bacteria consortia for space-efficient microalgal growth in a simple hydrogel system - Noah Martin; Tatum Bernat; Julie Dinasquet; Andrea Stofko; April Damon; Dimitri D. Deheyn; Farooq Azam; Jennifer E. Smith; Matthew P. Davey; Alison G. Smith; Silvia Vignolini; Daniel Wangpraseurt (Journal of Applied Phycology, 2021)
Photosynthetic microalgae are an attractive source of food, fuel, or nutraceuticals, but commercial production of microalgae is limited by low spatial efficiency. In the present study we developed a simple photosynthetic hydrogel system that cultivates the green microalga, Marinichlorella kaistiae KAS603, together with a novel strain of the bacteria, Erythrobacter sp. We tested the performance of the co-culture in the hydrogel using a combination of chlorophyll- a fluorimetry, microsensing, and bio-optical measurements. Our results showed that growth rates in algal–bacterial hydrogels were about threefold enhanced compared to hydrogels with algae alone. Chlorophyll- a fluorimetry–based light curves found that electron transport rates were enhanced about 20% for algal–bacterial hydrogels compared to algal hydrogels for intermediate irradiance levels. We also show that the living hydrogel is stable under different environmental conditions and when exposed to natural seawater. Our study provides a potential bio-inspired solution for problems that limit the space-efficient cultivation of microalgae for biotechnological applications.

Fate and Interaction with Soil N of Fertilizer 5N Applied to Wheat at Different Growth Stages - Muhammad Ashraf; Farooq-e-Azam (Cereal Research Communications, 1998)

Role of silicon in diatom metabolism - Farooq Azam; Benjamin E. Volcani (Archives of Microbiology, 1974)

Role of silicon in diatom metabolism - Farooq Azam; Barbara B. Hemmingsen; Benjamin E. Volcani (Archives of Microbiology, 1974)

Germanium incorporation into the silica of diatom cell walls - Farooq Azam; Barbara B. Hemmingsen; Benjamin E. Volcani (Archives of Microbiology, 1973)